Cyclophilin D deficiency attenuates mitochondrial perturbation and ameliorates hepatic steatosis. Issue 1 (9th May 2018) - Wang, Xiaolei; Du, Heng; Shao, Shanshan; Bo, Tao; Yu, Chunxiao; Chen, Wenbin; Zhao, Lifang; Li, Qiu; Wang, Li; Liu, Xiaojing; Su, Xiaohui; Sun, Mingqi; et al.
Abstract : Physiological opening of the mitochondrial permeability transition pore (mPTP) is indispensable for maintaining mitochondrial function and cell homeostasis, but the role of the mPTP and its initial factor, cyclophilin D (CypD), in hepatic steatosis is unclear. Here, we demonstrate that excess mPTP opening is mediated by an increase of CypD expression induced hepatic mitochondrial dysfunction. Notably, such mitochondrial perturbation occurred before detectable triglyceride accumulation in the liver of high‐fat diet–fed mice. Moreover, either genetic knockout or pharmacological inhibition of CypD could ameliorate mitochondrial dysfunction, including excess mPTP opening and stress, and down‐regulate the transcription of sterol regulatory element–binding protein‐1c, a key factor of lipogenesis. In contrast, the hepatic steatosis in adenoviral overexpression of CypD–infected mice was aggravated relative to the control group. Blocking p38 mitogen‐activated protein kinase or liver‐specific Ire1α knockout could resist CypD‐induced sterol regulatory element–binding protein‐1c expression and steatosis. Importantly, CypD inhibitor applied prior to or after the onset of triglyceride deposition substantially prevented or ameliorated fatty liver. Conclusion: CypD stimulates mPTP excessive opening, subsequently causing endoplasmic reticulum stress through p38 mitogen‐activated protein kinase activation, and results in enhanced sterol regulatory element–binding protein‐1c transcription and hepatic steatosis. (Hepatology 2018;68:62‐77).